Brazil still in troubled waters - Fernando J. Cardim de Carvalho (Levy Economics Institute of Bard College, 2017)
Since inheriting the Brazilian presidency five months ago, the new Temer administration has successfully ratified a constitutional amendment imposing a radical, two-decades-long public spending freeze, purportedly aimed at sparking an increase in business confidence and investment. In this policy brief, Fernando Cardim de Carvalho explains why this fiscal strategy is based not only on a flawed conception of the drivers of private-sector confidence and investment but also on a mistaken view of the roots of the current Brazilian economic crisis. The hoped-for 'expansionary fiscal consolidation' is not likely to be achieved.
Keywords: 330